Biologic therapy for inflammatory arthritis and latent tuberculosis: real world experience from a high prevalence area in the United Kingdom. Issue 12 (December 2015) - Nisar, Muhammad; Rafiq, Aneesa; Östör, Andrew
Abstract Biologic therapies have resulted in a sea change in the management of inflammatory arthritis; however, a higher risk of opportunistic infection, particularly tuberculosis (TB), is well recognised. This has led to the development of TB screening guidelines. The aim of this study was to investigate the prevalence of latent TB in patients prescribed biologic therapy in an endemic area (prevalence of TB 50/100, 000) and to assess the risk of subsequent reactivation. Retrospective case note review of all patients with inflammatory arthritis ever prescribed biologic therapy between 1998 and 2014 at our centre. Two hundred ninety-nine patients (109 men, 190 women) who had ever been prescribed biologic therapy over a 16-year period were included. Mean age upon commencing the biologic therapy was 51 years. Two hundred eighteen (73 %) patients were Caucasian with remaining from ethnic minorities. Two hundred thirty-nine (80 %) prescriptions were for TNF inhibitors. Median duration of biologic therapy was 4.2 years for those who remained on treatment prior to stopping or switching therapies. During 1998–2007, 112 patients underwent clinical assessment, chest X-ray and check for BCG scar. One patient of Asian origin developed extrapulmonary TB within 6 weeks of adalimumab initiation. Following a year of anti-TB treatment, he restarted the biologic therapy with no ill effects. One hundred eighty-seven participants (who started on biologic therapy between 2008 and 2014) underwent additional interferon gamma release assays (IGRA) testing as part of a new TB screening protocol (T -spot test). Eighteen (10 %) had positive test with normal chest X-rays. Six patients were white, nine of Asian origin and three others. Three Caucasian patients had a borderline result. All had 3 months of isoniazid and rifampicin with simultaneous prescription of biologic agent (13 had TNF antagonist, 5 rituximab and 3 tocilizumab). No cases of active TB infection were observed. Overall prevalence of latent TB in patients with inflammatory arthritis prescribed biologic therapy in an endemic area is 10 %. The risk warrants careful screening and monitoring in all patients. Adherence to strict screening protocol reduces the risk of active TB infection irrespective of the biologic therapy employed.